Teorija in empirija realne konvergence - Gramc, Boris (Naše gospodarstvo, 2006)
The article firstly explores two basic models that economists have usually used to study economic growth and real convergence issues. The first is the Solow-Swan growth model and the second is the AK-model. The Solow-Swan growth model shows that there exists a possibility of real convergence among countries and explains the reasons that one country grows faster than the other. The AK-model, on the other hand, shows that real convergence is not expected. The second part of the article is a survey of the literature and the most important empirical articles on real convergence issues. The survey chronologically presents empirical tests done by using different samples of countries all over the world. Most of the articles show that there exists some kind of convergence among countries, which means that poor countries are catching up with rich countries in the long run.
Keywords: gospodarska gibanja; konjunktura; gospodarska rast; konvergenca; modeli; ekonometrija